Monitoring of medical/health agencies designated as research centres in Nepal. (2018)
SUMMARY: Health research has led to significant discoveries, the development of new therapies, and a remarkable improvement in health care and public health around the world. Concisely, health research has made many significant breakthroughs in disease treatment and prevention and saved the lives of millions of people. Nepal Health Research Council (NHRC) is a national apical body of Government of Nepal for promoting health research in Nepal. The aim of NHRC is to maintain highest level of ethical standards and promote quality research enhancing research capacity in country. Being authorized body to regulate, monitor and coordinate health research centers of Nepal; NHRC had started to monitor the performance of health research centers throughout the country with an objective of assessing various research activities being conducted by Medical/Health Agencies designated as Research Centre in Nepal and also to ensure good ethical practices in health research are important to ensure that the dignity, rights, safety, and well-being of health research after all monitoring is also important for minimizing misuse of the word written as 'Research' in title of the health institutions. A cross sectional descriptive study design was used to carry out monitoring and follow up of activities of research centre of all seven provinces of Nepal that had title "Research" in their title name from January 2018 to July 2018. Initially, Company Registrar Office was contacted to collect relevant information of medical/health agencies (Hospitals, Polyclinics etc.) that has word "Research" in their title name. All the research centers were then grouped in their respective provinces and districts. The responsible persons of centers were contacted and their informed consent was taken and information was collected. Right after which twelve staff from NHRC was selected for monitoring and collecting the information from research centers all over Nepal and was provided intensive training before study. During training, emphasis was given on information collection procedures focusing on interview technique that used semi structured questionnaire contained with cover letter. After completion of data collection, questionnaires were checked for consistency and completeness. Data were entered into Epi Data 3.2 and cross tabulation were done using statistical package for social sciences (SPSS) version 17.0. Research found that 82.3% so called research centers were just health service provider and 10 % of research institute were research based and just 5% have the core objectives of research. Likewise, 30% of research institute were actually involved in health related researches whereas large proportion (70%) of research institute were not involved in any kind of research work. Surprisingly, only 37.5% have taken ethical approval to conduct the designated research. It has been concluded that there were 370 research centers presented in Nepal from the information provided by the Office of Company Registrar Tripureswor, Kathmandu (As per low every private institution must be register their firm before operating any kind of business in OCR. It was also found that there are disparities in the availability of the research center. So, strategic policy should be incorporated for equal involvement. Similarly, organizations whose core objectives are to provide health services are more active in research rather than research organization itself. Furthermore, most of the research organizations want to conduct research but they do not have required research skills and competent manpower at their institutions to carry out research.